Pelletizing ultra-high molecular weight polyethylene (UHMWPE) powders with a novel tapered die and addition of high density polyethylene (HDPE): Processing, morphology, and properties. (21st September 2022) - Yang, Huaguang; Yilmaz, Galip; Jiang, Jing; Xie, Jun; Langstraat, Thomas; Chu, Raymond; van Es, Martin; Garg, Priya; Turng, Lih-Sheng
Abstract: The extremely high molecular weight and molecular entanglement have rendered ultra-high molecular weight polyethylene (UHMWPE) superior properties. However, poor inter-particle diffusion makes it difficult to pelletize UHMWPE powders for easy processing/handling. A novel tapered die with air cooling was proposed to pelletize UHMWPE and a UHMWPE blend with 5 wt% high-density polyethylene (HDPE) for compression molding and material characterization. The tensile strength of samples prepared with the tapered die outperformed those by the regular die or from virgin powders. The addition of HDPE further improved the tensile strength. Fourier transform infrared spectroscopy (FTIR) revealed little chain scission and the lowest amount of oxidation from the tapered die. Intrinsic viscosity (IV) measurements confirmed the negligible chain scission and showed an increment in IV for the UHMWPE/HDPE blend. Multi-angle light scattering with size-exclusion chromatography (SEC-MALS) indicated no change in the UHMWPE molecular weight distribution, but some crosslinking in the blend. Polarized optical microscopy (POM) showed that the HDPE and extrusion led to a finer UHMWPE domain size and better fusion between UHMWPE and HDPE. The combined effect of enhanced molecular chain diffusion, improved consolidation, and lower oxidation using the tapered die led to 40% improvement of tensile strength for the UHMWPE/HDPE blend. Graphical abstract: Image 1 Highlights: Neat UHMWPE powders were successfully pelletized using a regular twin-screw extruder. A novel tapered die with air cooling led to noticeable improvement in tensile strength. Blending 5 wt% HDPE with UHMWPE by the tapered die improved the tensile strength by 40%. The increased tensile strength and molecular weight are attributed to the crosslinking and enhanced molecular diffusion.